HUBUNGAN PAPARAN KEBISINGAN DAN KARAKTERISTIK INDIVIDU DENGAN KELAINAN TEKANAN DARAH PENGEMUDI BECAK BERMOTOR DI KECAMATAN MEDAN JOHOR KOTA MEDAN TAHUN 2017 - FITHRI HANDAYANI LUBIS; Rizka Annisa (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2018)
Noise is unwanted sound from an activity which could cause disruption of human health and comfort environment. The impact of noise are physiological disturbances, psychological, communication and effects of hearing loss. At this time the noise began to increase in the community as of physical development activities as a means of transport, should be controlled noise level so to exceed the limits. The objective of this study is to know The relationship of exposure to noise and the individual characteristics of Becak Bermotor driver with blood pressure on Kecamatanamatan Medan Johor, Kota Medan in 2017. Type of research is a survey which has analytic with cross secsional design. The variables measured were the characteristics of the driver, the noise exposure and blood pressure. The population in this research is the driver Becak Bermotor, which conducted to 35 persons and a sample of 31 people. Research is analyzed with test chi-square. The result of research show that there is a significant relationship between noise intensity with blood pressure (p <0,05) with strength value 0,020. There was a significant relationship between the duration of noise exposure and the use of helmets with blood pressure (p <0.05) with chi-square test, with value value 0.001. There was a significant relationship between coffee drinking habits and smoking with blood pressure (p <0.05) with a strength value of 0.002.